1987
DOI: 10.1007/bf02540794
|View full text |Cite
|
Sign up to set email alerts
|

Dry extrusion as an aid to mechanical expelling of oil from soybeans

Abstract: A new concept is described for mechanical extraction of oil from soybeans, using dry extrusion as a pretreatment. It was found that coarsely ground whole soybeans at 10 to 14% moisture could be extrusion cooked so that the extrudate emerges from the die in a semi‐fluid state. The dwell time within the extruder was less than 30 seconds, and the temperature was raised to about 135 C. The semi‐fluid extrudate was immediately pressed in a continuous screw press to obtain high quality oil and press cake. Extrusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
1
2

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(71 citation statements)
references
References 2 publications
2
66
1
2
Order By: Relevance
“…LFSF is defined as having 5 to 6% residual fat (5). A significant number of small soybean processors, those that process between 6 and 120 tons of soybeans per day, utilize this technology because of the low capital investment costs, enhanced extraction capabilities, and the ability to produce oxidatively stable oils and meals low in FFA (4).…”
mentioning
confidence: 99%
“…LFSF is defined as having 5 to 6% residual fat (5). A significant number of small soybean processors, those that process between 6 and 120 tons of soybeans per day, utilize this technology because of the low capital investment costs, enhanced extraction capabilities, and the ability to produce oxidatively stable oils and meals low in FFA (4).…”
mentioning
confidence: 99%
“…This is in line with the results of Ruiz et al (2004) who established, in a trial with broilers fed extruded FFSBs, that body weight gain and FCR were best for treatment temperatures between 126 °C and 140 °C. Nelson et al (1987) stated that temperatures most commonly used commercially for extruding raw soybeans were between approximately 135 °C and 140 °C. Palic et al (2009) concluded from two separate trials with broilers that the optimum heat treatment of FFSBs was at 138 °C and 144 °C.…”
Section: Discussionmentioning
confidence: 99%
“…Methods of processing soybean and variations in processing also contribute to the overall quality of the soybean products. These include extrusion and expelling, solvent extraction (Woodworth et al, 2001;Nelson et al, 1987), roasting and Jet-sploding (Marty et al, 1994;Subuh et al, 2002), and micronization (Marty et al, 1994;Subuh et al, 2002). These methods lead to variations in nutrient composition of the final product (s).…”
Section: Nutritional Value Of Soybeans and Soybean By-productsmentioning
confidence: 99%